In-situ SEM analysis of plastic deformation, crack initiation, crack propagation behaviors in M2 high speed steel - Lihui Zhu; Weiwei Zhang; Ruiyun Shi; Guoliang Wang (Journal of Materials Research and Technology)
The plastic deformation, crack initiation, crack propagation behaviors of M2 high speed steel were investigated by means of in-situ SEM observation during tensile. The effect of tempered martensite, retained austenite and carbides on the deformation and fracture of M2 steel was discussed. Results show that crack initiation initially takes place in the matrix, at the interface of carbide and matrix. After almost all the plasticity deformation capability is exhausted, the cracks begin to initiate in the carbides. The matrix helps to impede the crack propagation, since some cracks initiated in the carbides or at the interface either stop or get deflected in the matrix. The crack branching and crack deflection in the carbides are beneficial to slow down the crack propagation. Most matrix-related cracks are involved in blocky retained austenite. The crack initiation and propagation are affected by the type, shape and size of carbides. Primary carbides and those carbides with large size and sharp edges promote the crack initiation and propagation. Among all the carbides, primary M6C is the most harmful. To improve the toughness of M2 steel, it is suggested that the number and size of blocky retained austenite should be decreased. Meanwhile, reducing the number of primary M6C, decreasing the size of carbides and modifying the shape of angular carbides are favorable. Our investigation offers valuable insights for the toughness improvement of M2 steel.